Świadczenia ekosystemów jako rozwijające się pole badawcze i aplikacyjne - Mizgajski, Andrzej (Wydawnictwo Ekonomia i Środowisko, 2010)
A transdisciplinary insight into natural and economic functions of ecosystems and the resulting benefits can play a major role in a better consideration of nature related premises when making decisions in an economic dimension. This paper is a synthetic overview of the development of studies and current world research trends in the newly developing field referred to as ecosystem services. Its objective is to induce in Poland a broader interest in the field among both economists and nature scientists. The paper presents the main research and application trends as well as relations between the economic and nature streams in the study on ecosystem services.
Ecosystem services as an emerging field of research and application
Keywords: environmental management; ecosystem services; environmental value